2021
DOI: 10.3389/fmolb.2021.668888
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Immunity and Therapeutic Sensitivity Analyses Based on Differential Genomic Instability-Associated LncRNAs in Left- and Right-Sided Colon Adenocarcinoma

Abstract: Background: The purpose of our study was to develop a prognostic risk model based on differential genomic instability-associated (DGIA) long non-coding RNAs (lncRNAs) of left-sided and right-sided colon cancers (LCCs and RCCs); therefore, the prognostic key lncRNAs could be identified.Methods: We adopted two independent gene datasets, corresponding somatic mutation and clinical information from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases. Identification of differential DGIA lncRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Our study identified 29 prognosis-associated, m6A-related lncRNAs based on data from 379 COAD patients, and 12 of them were used to construct the m6A-LPS. NKILA and BOLA3-AS1 have been identified as unfavorable factors for colon cancer (Xu et al, 2021a;Guo et al, 2021;Chen et al, 2022;Qiu et al, 2022), which is consistent with the findings of this study. PCED1B-AS1 was reported to promote the proliferation of COAD by regulating the miR-633/HOXA9 axis, which was proven by in vitro and in vivo experiments (Liu et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Our study identified 29 prognosis-associated, m6A-related lncRNAs based on data from 379 COAD patients, and 12 of them were used to construct the m6A-LPS. NKILA and BOLA3-AS1 have been identified as unfavorable factors for colon cancer (Xu et al, 2021a;Guo et al, 2021;Chen et al, 2022;Qiu et al, 2022), which is consistent with the findings of this study. PCED1B-AS1 was reported to promote the proliferation of COAD by regulating the miR-633/HOXA9 axis, which was proven by in vitro and in vivo experiments (Liu et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Four lncRNAs (ARRDC1-AS1, OIP5-AS1, BOLA3-AS1, and NIFK-AS1) were mentioned in previous COAD studies. 59 62 Collectively, these factors may lead to the further exploration of COAD progression and can be investigated as biomarkers and therapeutic targets for COAD.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers once constructed a signature that had the prognosis ability of UCEC in light of five glycolysis-related lncRNAs, including BOLA3-AS1 [37]. BOLA3-AS1 could also participate in the construction of models to predict the prognosis of gastric cancer, as well as left-sided and right-sided colon cancers [79,80]. AC006329.1 has great potential for assessing risk and supplying personal treatment for colon cancer patients [81].…”
Section: Discussionmentioning
confidence: 99%